Poetics of Justice: Using Art as Action and Analysis in Participatory Action Research - Jennifer Ayala; Mayida Zaal (Networks: An Online Journal for Teacher Research, 2016)
This article explores the use of art as a form of communication and meaning-making in participatory action research (PAR). The authors, researchers and educators, contemplate this concept through a pedagogical lens, and consider the role that visual and performing arts can play in social action. Based on the work of a youth-adult participatory action research collective, the authors reflect on the pedagogical process used to analyze research findings, take actions, and affect local change. Created to investigate opportunity to learn issues, the youth members of the collective created spoken word poetry, post-cards, film shorts, and speak-outs to engage multiple audiences in their research findings. By engaging art as an element of PAR, actions can travel visually, viscerally, and verbally with the potential to influence individuals, communities, and policies.
Keywords: art; participatory action research (PAR); education policy; youth research; community-based research